(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital trends in social and economic development change the labour concepts and attitudes towards careers. Through the life course people more often change their job, residence, specialty. That circumstance implies the need for new skills or retraining within the space of lifetime. This study is based on the assessment of the continuity of Azerbaijani education in the digital economy. The work was performed within the framework of the methodology proposed by the World Bank and aimed at interpreting and combining particular outputs of statistical studies, since a comprehensive statistical survey of the digitization of education has not yet been carried out. The results, on the one hand, indicate great promise in terms of system enhancements and expansion of lifelong education opportunities for all categories of citizens through development of the Azerbaijani digital space and increase the number of training organizations. On the other hand, the development of this direction is weak and of an ad hoc nature: specific goals and objectives, supply and demand, formal and informal methods in each field of Azerbaijani education are not fully taken into account.